1982
DOI: 10.1001/archderm.118.5.346
|View full text |Cite
|
Sign up to set email alerts
|

Solar urticaria. Determinations of action and inhibition spectra

Abstract: A 42-year-old woman acquired solar urticaria approximately ten minutes after exposure to sunlight. Urticaria developed from visible light emitted from a projector lamp after a similar time lag. Monochromatic rays between 400 and 500 nm induced immediate urticaria by irradiation, with four times the minimal urticarial dose. Urticaria that was induced by monochromatic rays of the projector lamp was completely inhibited by immediate reirradiation of test sites with light waves longer that 530 nm. Radiant heat exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 3 publications
4
34
0
1
Order By: Relevance
“…IS were first reported by Hasei and Ichihashi [1]and have been found mainly in Japanese patients with solar urticaria [2]. The IS observed in our cases displayed unique characteristics, that is, it prevented wheal formation during IS irradiation and wheals developed after cessation of the irradiation.…”
Section: Introductionmentioning
confidence: 50%
“…IS were first reported by Hasei and Ichihashi [1]and have been found mainly in Japanese patients with solar urticaria [2]. The IS observed in our cases displayed unique characteristics, that is, it prevented wheal formation during IS irradiation and wheals developed after cessation of the irradiation.…”
Section: Introductionmentioning
confidence: 50%
“…An inhibition spectrum was first demonstrated in solar urticaria by Hasei and Ichihashi [3], who observed that the irradiation by longer wavelengths than the action spectrum, immediately after the exposure to urticaria-eliciting light, inhibited the development of urticaria. This phenomenon is not uncommon [8] and has been confirmed by other inves tigators [9 -11], On the other hand, the augmentation spec trum has been demonstrated so far in only 1 patient which was reported by Horio and Fujigaki [4J.…”
Section: Discussionmentioning
confidence: 98%
“…A patient who showed a marked broadening of the action spectrum was also documented by Murphy and Hawk |2). In addition, the inhibition [3] and augmentation spectra [4] were also found to be present in certain cases of solar urticaria. Consequently, various wave-lengths seem to affect the reaction of solar urticaria in com plicated interactions.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, a case of solar ur ticaria with inhibition spectrum was report ed [3], and wealing in the patient was com pletely inhibited by exposure to visible light above 690 nm. We also encountered a simi lar patient showing an inhibition spectrum in the red light range (visible light longer than 660 nm).…”
mentioning
confidence: 99%